Risk of hospitalisation for first-onset psychosis or mania within a year of ADHD medication initiation in adults with ADHD - Ragna Kristin Gudbrandsdottir; Engilbert Sigurdsson; Þorsteinn Ivar Albertsson; Halldora Jonsdottir; Oddur Ingimarsson (BMJ Mental Health)
Background The prevalence of attention-deficit hyperactivity disorder (ADHD) drug treatment for youth and adults has been rising exponentially in Iceland over the past 15 years. The efficacy of ADHD drugs is not as strongly supported for adults as for children and adolescents, and adult use has been reported to increase the risk of psychosis or mania.Objective To assess the absolute risk of hospitalisation for first-onset psychosis or mania in adults diagnosed with ADHD within 1 year of being prescribed ADHD drugs and to examine the proportional attributable risk.Methods This study included all adults prescribed ADHD drugs in Iceland between 1 January 2010 and 31 December 2022. Records from the Icelandic Prescription Drug Register were linked to the Hospital Discharge Register to identify individuals who were admitted due to psychosis or mania. This risk was compared with the risk of all other first-onset hospitalisations for psychosis, mania or mixed episodes between 1 January 2018 and 31 December 2020.Findings 16 125 individuals aged 18 or older initiated ADHD drug therapy during the study period. Of those, 61 were hospitalised due to first-onset psychosis or mania within a year. This corresponds to an absolute risk of 0.38% for such an admission. The general population risk for all other first-onset hospitalisations for psychosis or mania from 2018 through 2020 for Icelanders aged 18–67 was 0.048%. The estimated relative risk was 7.99 (95% CI 6.06, 10.54), the proportional attributable risk 87.5% and the number needed to harm 302 (95% CI 271, 340). Within 1 year of hospital discharge, 69% (42/61) had been represcribed their ADHD medication, and 26.2% (11/42) of these had to be readmitted for psychosis or maniaConclusions The risk of hospitalisation for psychosis or mania with prescription ADHD drugs is small but real among adults, and represcription is strongly associated with readmission.Clinical implications Clinicians and adults diagnosed with ADHD should be aware of the association between ADHD drugs and the risk of developing psychosis or mania requiring hospitalisation in adults with ADHD.